Penerapan Pengembangan Kurikulum Berbasis Edukotourism di Madrasah Tsanawiyah Negeri 3 Pamekasan - Hasanah, Uswatun (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The development of the edukotourism curriculum is implemented by MTs Negeri 3 Pamekasan which aims to create an environment-based environment-based enjoy full learning environment. This research includes the planning, implementation, and evaluation of the application of the edukotourism curriculum at MTs Negeri 3 Pamekasan. This research uses a qualitative research method with a descriptive approach and is a type of case study research. Sources of data obtained from interviews, observation and documentation. The results of the study show that: First, the planning for the implementation of educotourism curriculum development at MTsN 3 Pamekasan relies on curriculum planning through a subject-class approach that starts from the formation of subject schedules by taking into account the distribution of subjects, educational calendars, lesson plans and syllabus as learning tools to be used. Second, the implementation of educational tourism curriculum development at MTsN 3 Pamekasan is emphasized through environmental culture in madrasas with programs that support students' level of concern for their environment. Third, the evaluation carried out by MTsN 3 Pamekasan uses supervision of class visits, namely direct observation of the edukotourism-based learning process.